New State of MCDM in the 21st Century Selected Papers of the 20th International Conference on Multiple Criteria Decision Making 2009 - Shi, Yong 1956-; Wang, Shouyang; Kou, Gang; Wallenius, Jyrki (Lecture notes in economics and mathematical systems, 2011)
This book provides cutting-edge research results and application experiences from researchers and practitioners in multiple criteria decision making areas. It consists of three parts: MCDM Foundation and Theory, MCDM Methodology, and MCDM Applications. In Part I, it covers the historical MCDM development, the influence of MCDM on technology, society and policy, Pareto optimization, and analytical hierarchy process. In Part II, the book presents different MCDM algorithms based on techniques of robust estimating, evolutionary multiobjective optimization, Choquet integrals, and genetic search. In Part III, this book demonstrates a variety of MCDM applications, including project management, financial investment, credit risk analysis, railway transportation, online advertising, transport infrastructure, environmental pollution, chemical industry, and regional economy. The 17 papers of the book have been selected out of the 121 accepted papers at the 20th International Conference on Multiple Criteria Decision Making "New State of MCDM in 21st Century", held at Chengdu, China, in 2009. The 35 contributors of these papers stem from 10 countries.